2016
DOI: 10.1634/theoncologist.2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Antidrug Antibody Formation in Oncology: Clinical Relevance and Challenges

Abstract: Because of the increasing use of biologicals in oncology, many patients are at risk of developing antidrug antibodies (ADAs) during therapy. Although clinical consequences are uncertain, ADAs may affect pharmacokinetics, patient safety, and treatment efficacy. ADA detection and reporting is currently highly inconsistent, which makes it difficult to evaluate the clinical consequences. Standardized reporting of ADA investigations in the context of the aforementioned parameters is critical to understanding the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 69 publications
3
78
0
1
Order By: Relevance
“…It is relevant that anti-drug antibodies have been reported in many trials using recombinant proteins and antibodies. 24 In one study, anti-IL-2 antibodies were detected in roughly half of patients, and development of these antibodies was not associated with a decrease in the treatment effect. 25 …”
Section: Discussionmentioning
confidence: 95%
“…It is relevant that anti-drug antibodies have been reported in many trials using recombinant proteins and antibodies. 24 In one study, anti-IL-2 antibodies were detected in roughly half of patients, and development of these antibodies was not associated with a decrease in the treatment effect. 25 …”
Section: Discussionmentioning
confidence: 95%
“…We postulate that an antidrug antibody (ADA) has the potential to induce Fc receptor binding similar to an IgG cross-linker and induce degranulation. Because detection of ADA has been reported in 26% of oncology patients treated with a fully humanized antibody (39), an Fc-silent antibodies approach would likely not be feasible in the clinic because of the risk of ADA.…”
Section: Discussionmentioning
confidence: 99%
“…67 The report also found that even among agents on the market, gaps in the data on ADA formation were apparent. 67 Routine investigation of the relationship between ADAs and efficacy, toxicity, and PK may shed light on the clinical relevance of ADAs and help explain the variability seen in drug responses and safety. Standardized reporting of ADAs is critical to understanding the relevance of ADA formation, and the development of trials investigating clinical prevention strategies is needed.…”
Section: Antidrug Antibodiesmentioning
confidence: 99%
“…ADAs can also have toxic effects, including hypersensitivity reactions . A recent ADA‐focused review of extracted data from 81 oncology clinical trials of biologic agents reported most biological anticancer immunotherapy drugs are immunogenic and induce ADAs . The report also found that even among agents on the market, gaps in the data on ADA formation were apparent .…”
Section: Mechanisms Of Resistance To Cd3‐bispecific Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation